The Effect on Using Different Types of Electrodes toward the Tensile Strength of the Welding Joints Groove V Low Carbon Steel Type DIN 1.0038 - Fernando, Yogi; Mulyadi, Rodesri; Ambiyar, Ambiyar (Universitas Negeri Padang, 2020)
The choice of electrode type in welding will affect the strength of the welding result. The aim of this study was to determine the effect on using different type of electrode on the tensile strength of low carbon steel type 1.0038 by using experimental method. The welding was conducted using Groove V. In addition, the specimens used in this research were the low carbon steel plate type 1.0038 with a thickness of 8 mm and were given SMAW treatment using 2 different types of electrodes, namely E 6013 and E 7016 whose diameters were 2.6 and 3.2 mm. The standard specimen used was ASTM-E8 and being tested using a Universal Testing Machine. Based on the research that had been conducted, it was obtained that the steel type 1.0038 welded using E 7016 electrodes had a higher tensile strength than the one using E 6013.